Geotechnical properties and morphological properties of raw and processed Gebeng bauxite - Phang, Biao Yu (2017)
This research is to identify the differences between the geotechnical properties of raw and processed Gebeng bauxite. Raw bauxite deposits usually contain a higher percentage of clay and siliceous materials. The silica present in the bauxite usually are concentrated in the finer grained fraction of the bauxite deposit. The fine particles in bauxite will cause the bauxite to have higher moisture content and increases the risk of liquefaction to occur during the bauxite’s transportation in cargo. The main objective of having beneficiation process before cargo transporting is to minimize the silica content which contributes to the finer fraction in bauxite, as well as to improve the geotechnical properties of bauxite so that it passes the specification of International Maritime Solid Bulk Cargoes Code (IMSBC) for cargo shipping purpose. In this research, a series of laboratory tests will be conducted and the results will reflect the geotechnical properties of Gebeng Bauxite and the correlation of the bauxite’s properties can be done. Both the raw and processed Gebeng Bauxite samples will undergo moisture content test, specific gravity test, particle size distribution, Field Emission Scanning Electron Microscope (FESEM) and X-ray fluorescence (XRF) to obtain the desired data.